Linguagem, consciência e ideologia na formação do sujeito histórico-social em Mikhail Bakhtin - Aguiar, Francisco Brandão (2023)
Mikhail Mikhailovich Bakhtin (1895 -1975) approach the most varied themes related to Human Sciences. It is through his multifaceted theoretical approach that Bakhtin writes about issues related to the subject. However, this thinker did not write any pamphlet, book or article expressly dedicated to this category. The formation of the subject, in the thought of Mikhail Bakhtin, is a theme that runs through many of his works and has as a strong characteristic the influence of the historical context and the social environment. Furthermore, this theme is addressed more frequently in relation to three other concepts, namely: language, consciousness and ideology. In this sense, this thesis aims to understand how the formation of the historical-social subject takes place from the concepts of language, conscience and ideology in the thought of Mikhail Bakhtin. In a general sense, I work with the hypothesis according to which, the currents that approached the category of the subject did not understand it in the dialectical perspective, but rather unilaterally (subjectively and abstractly). I intend to show that the concepts of language, conscience and ideology, as constitutive elements of the formation of the subject, are not worked in a way to consider the historical-social aspect of the subject. It is essential to point out that, from this emerges the importance of Bakhtin for education, because, through his writings, it is possible to evidence the commitment that education must have in working with a conception of the subject as a being conceived from its context real and socio-historical. This research is characterized as bibliographical, qualitative and is developed through critical-discursive interlocution. I conclude that: Based on Bakhtinian thought, it is possible to delineate the concept of subject as being something socially and historically contextualized. It is a category that arises as a result of a dialectical synthesis of the reality that surrounds it, and this reality conditions, mainly, three aspects that are constitutive of its formation: language, conscience and ideology. Consciousness is an attribute of the subject, one of its constitutive elements. Language is personified in its function as a sign and becomes the means of expression of the subject's inner activity. ideology is inherent to the linguistic sign, where there is a sign there is ideology. Furthermore, the thesis demonstrates Bakhtin as an irrecusable thinker for education. In this sense, bringing up the issue of the subject as a being of dialogue, as a being who has a conscience that reflects external reality and is permeated by an ideological context, it is something that education must take into account when building its processes.